2010
DOI: 10.1073/pnas.1005173107
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput method for analyzing methylation of CpGs in targeted genomic regions

Abstract: A unique microarray-based method for determining the extent of DNA methylation has been developed. It relies on a selective enrichment of the regions to be assayed by target amplification by capture and ligation (mTACL). The assay is quantitatively accurate, relatively precise, and lends itself to high-throughput determination using nanogram amounts of DNA. The measurements using mTACLs are highly reproducible and in excellent agreement with those obtained by sequencing (r = 0.94). In the present work, the met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…%5mC levels of individual CpG dinucleotides were averaged to obtain a mean measure for each of the assays. The basis for using the average was the observation that methylation values in adjacent CpG sites over a short amplicon such as that used in pyrosequencing analysis are usually highly correlated [36]. In our previous work, we observed that averages of DNA methylation within each amplicon provide more robust methylation measures compared with analyses of individual CpGs [37].…”
Section: Methodsmentioning
confidence: 99%
“…%5mC levels of individual CpG dinucleotides were averaged to obtain a mean measure for each of the assays. The basis for using the average was the observation that methylation values in adjacent CpG sites over a short amplicon such as that used in pyrosequencing analysis are usually highly correlated [36]. In our previous work, we observed that averages of DNA methylation within each amplicon provide more robust methylation measures compared with analyses of individual CpGs [37].…”
Section: Methodsmentioning
confidence: 99%
“…In genome wide studies in both normal and cancerous colon tissue, irrespective of the genomic locus, Nautiyal et al observed a very high correlation in methylation levels that decreased as the distance between dinucleotides increased. 43 Over the scale of a typical promoter, they observed a linear decrease in the Pearsons' r from > 0.8 for dinucleotide pairs less than 50 bp apart to < 0.4 for pairs 1 kb apart. Chronic stress increased methylation levels significantly in the pituitary and adrenal glands, and in both tissues a promoter-wide regulation was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the correlation in methylation between CpG sites appears to be a function of the distance between sites, consistent with the findings of Nautiyal and colleagues. 23 This relatively high degree of correlation suggests that use of the mean may be a reliable marker of the extent of methylation across this region.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%